Rate, Maternal and Fetal Outcome of Cesarean Delivery Performed by IESO at Shenen Gibe General Hospital, Jimma South West Ethiopia: A Descriptive Retrospective Data - Worku, Gebeyehu Gutema; Teshome, Kassa Jire; Daniel, Aboma (Journal of Women's Reproductive Health, 2020)
Background Pregnancy and parturition are events of considerable significance in the life cycle of women. Though it is supposed that the quality of care during labor, birth, and postpartum period plays a great role for adverse outcomes of birth, various reports claimed that cesarean delivery carries a higher maternal and fetal morbidity and mortality compared to vaginal delivery. Therefore, this study assessed the Rate, Maternal and Fetal Outcome of Cesarean delivery performed by IESO at Shenen Gibe General Hospital, Jimma south west Ethiopia. Integrated Emergency surgical officer is a health professional qualified and authorized to perform emergency obstetrical-gynecological and emergency general surgical procedures. The training has started in 2010 in 3 universities and 10 affiliated sites with intake of 43 students. The MSc program in integrated emergency surgery is intended to achieve one of the millennium development goals (MDG): reducing the overwhelming maternal mortality ratio and perinatal mortality rate at the local and national level. (1) Methods Hospital based two-year retrospective descriptive cross-sectional study design was employed and data collected from November to December 2019 in shenen Gibe General Hospital ,Jimma south west Ethiopia. A total of 185 mothers who delivered by cesarean delivery from December 2017 to December 2018 and complete data were included in the study. Data were extracted using structured data collection format and cleaned, and entered into Epi data software version 3.1 and exported into SPSS version 26 for further descriptive analysis. Result Among 2115 deliveries in the two years of retrospective data, a total of 186 mothers were delivered by cesarean section, giving cesarean delivery rate 8.8 %. The leading indication for cesarean delivery was fetal distress (24.2%). Among the total cesarean delivery, 22 neonates were died, giving the proportion of neonate mortality rate 16.8%. One mothers were died following cesarean delivery, giving maternal mortality rate following cesarean delivery 12 per 1000 live births. The leading cause for maternal mortality was hemorrhagic shock Conclusion However, cesarean delivery rate in this study was within the WHO recommended range, the health outcome of mothers and neonates’ following cesarean delivery was not acceptable. The neonatal and maternal mortality following cesarean delivery was 16.8% and12 per 1000 live births respectively. The main cause of neonatal death was birth asphyxia.
Keywords: Cesarean delivery rate; maternal and neonate outcomes; IESO; cross sectional & south west Ethiopia.